2012
DOI: 10.1021/es303889z
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Reactions of Particulate Methoxyphenols with NO3 Radicals: Kinetics, Products, and Mechanisms

Abstract: Methoxyphenols, tracers for wood smoke, are emitted into the atmosphere in large quantities, but their chemical degradation in the atmosphere has not been well characterized. In this study, heterogeneous kinetics of particulate syringaldehyde (SA), vanillic acid (VA), and coniferyl aldehyde (CA) with NO3 radicals is investigated with a mixed-phase relative rate method. A vacuum ultraviolet photoionization aerosol time-of-flight mass spectrometer and an atmospheric gas analysis mass spectrometer are used to mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
71
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(72 citation statements)
references
References 59 publications
(176 reference statements)
0
71
1
Order By: Relevance
“…Furthermore, the intermediate radical I was transformed into 4-hydroxy-3-methoxyacetophenone through a series of reactions given in the scheme and proposed in ref 54. A previous study suggested that a double bond could be formed through the 52 Similarly, in this reaction, intermediate I can also reaction with NO 3 to form 1-guaiacylethyl-1 nitrate. 2-Methoxy-4-vinylphenol was then formed through the elimination of nitric acid.…”
Section: Resultsmentioning
confidence: 96%
“…Furthermore, the intermediate radical I was transformed into 4-hydroxy-3-methoxyacetophenone through a series of reactions given in the scheme and proposed in ref 54. A previous study suggested that a double bond could be formed through the 52 Similarly, in this reaction, intermediate I can also reaction with NO 3 to form 1-guaiacylethyl-1 nitrate. 2-Methoxy-4-vinylphenol was then formed through the elimination of nitric acid.…”
Section: Resultsmentioning
confidence: 96%
“…Category 2 products ([M-14] + ) were derived from the transformation of the methoxy (-OCH 3 ) group into the hydroxyl (-OH) group. This transformation has been observed by photolysis and NO 3 -initiated oxidation of vanillic acid (Net et al, 2011;Liu et al, 2012). Category 3 products ([M + 14] + ) resulted from either transformation of the hydroxyl (-OH) group into the methoxy (-OCH 3 ) group or the formation of quinone at C1 and C4 position.…”
Section: Oxidation Productsmentioning
confidence: 88%
“…The nitro-products were identified, and they are suspected constituents of atmospheric "brown" carbons. Other studies have been published on the heterogeneous ozonolysis of methoxyphenols adsorbed on silica particles (Net et al, 2010a(Net et al, , 2010b(Net et al, , 2011, aqueous-phase ozonolysis of methoxyphenols in solutions (Khudoshin et al, 2008;Ko et al, 2011), heterogeneous nitration of suspended methoxyphenol particles by reaction with NO 3 radicals (Liu et al, 2012), and heterogeneous oxidation kinetics of biomass-burning aerosol surrogates reacting with a series of atmospheric oxidants (Knopf et al, 2011). To the best of our knowledge, no study on the gas-phase reactions of methoxyphenols with NO 3 radicals has been reported, nor have their reaction mechanisms been delineated so far.…”
Section: Introductionmentioning
confidence: 99%
“…Other significant products from burning grasses are acetosyringone, syringic acid, vanillin and vanillic acid. Methoxy phenols degrade in the atmosphere, where 2-methoxyphenol (guaiacol) and its isomers in the gas-phase react with OH hydroxyradicals (Coeur-Tourneur et al, 2010), while phenols react with 3 C ⁎ (aromatic carbonyl) and some methoxy phenols in particulate matter react with O 3 (Net et al, 2011), NO 3 (Liu et al, 2012), 3 C ⁎ , OH (Li et al, 2014;Yu et al, 2014), and UV (Li et al, 2014). Most previous determinations of PCs in aerosols were performed in zones close to residential areas using biomass burning in domestic heating (Bari et al, 2010(Bari et al, , 2011Dutton et al, 2009Dutton et al, , 2010He et al, 2010;Simpson et al, 2005;Ward et al, 2011) or else in zones heavily impacted from wildfire smoke (Ward et al, 2006).…”
Section: Introductionmentioning
confidence: 99%